Development and validation of a hybrid measure of organisational communication satisfaction - Amanuel Gebru Woldearegay; George Angelopulo; Seleshi Zeleke Teketel (Communicare)
The purpose of the study was to develop a hybrid quantitative audit of organisational communication satisfaction for the public service. In Study One, a two-factor solution was obtained, based on parallel analysis as a factor determination strategy with data obtained from 264 civil servants using a 30 item measure. In Study Two, the items of the new EFA-generated organisational communication satisfaction scale were renumbered consecutively and the scale was crossvalidated on a new sample of 288 civil servants from the Addis Ababa City Administration. The cross-validation necessitated model respecification and re-estimation. The respecified model underwent validation at different levels. All seven aspects of validity, namely content validity, construct validity, factorial validity, reliability, convergent validity, discriminant validity and nomological validity were addressed and found to be adequate, pointing to a refinement in the measurement of communication satisfaction. However, limitations are also indicated as avenues for further enquiry.